Context of scientific publications in regionally indexed journals versus global publications - Barrutia Barreto, Israel (2021)
Introduction: The objective of this research was to deepen the results obtained in the systematic review of references, in high impact publications, placed in journals indexed in high level databases, such as: Scopus and Web of Science (WoS) compared to publications of the same. impact, but in the global context. Method/Results: The research method (descriptive-documental) was used, taking as a reference articles related to the theme. Therefore, the results showed that in Peru and Ecuador, countries that are going up in these databases, we have only 14 Peruvian journals indexed in WoS and 9 in Scopus, for Ecuador their journals indexed in WoS reach 20, while for Scopus, is reduced to just 2 magazines. Conclusion: According to these data, the measures taken by the two countries to increase their scientific proliferation and the extent to which the State contributes to this academic-professional.